Strategi Pemberdayaan Masyarakat dalam Mitigasi Bencana Melalui Jabar Resilience Culture Province di Jawa Barat Community Empowerment Strategy in Disaster Mitigation Through West Java Resilience Culture Province in West Java - Kusumawati, Riny (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2024)
The West Java Resilience Culture Province (JRCP) program is designed to foster aculture of disaster awareness and resilience among the people of West Java in their response todisasters. JRCP aims to create a prepared society by leveraging technology and infrastructuredevelopment as effective mitigation measures. Community empowerment plays a vital role indisaster mitigation, facilitating individuals, families, and communities to take responsibility fordisaster risk reduction. This approach also develops their ability to actively participate in disasterrisk reduction efforts, fostering a motivation to recognize and address potential disaster threatsand risks. The research focuses on two main aspects which are building community awareness indisaster mitigation and enhancing community capacity for disaster response. A qualitativeapproach using the case study method is employed for this research. Informants were selectedthrough purposive sampling, ensuring they met specific research criteria. Data collectioninvolved interviews, and the analysis was carried out using descriptive analysis techniques. Theresearch findings highlight the various approaches to community empowerment in disastermitigation. These include building community awareness through targeted socialization activitiesto impart knowledge about disaster risks and their management.Keywords: Community, disaster awareness, disaster mitigation.